Sources of stress, coping strategies and social support among seafarer of Leon, Iloilo. - Batin, Hazel C.; Torilla, Hanna Mae. (2009.)
The study sought to determine the sources of stress
Thesis (Undergarduate, Bachelor of Arts in Psychology-Management) College of Arts and Sciences, University of the Philippines Visayas, Miag-ao, Iloilo.
Keywords: Seafarers